The role of trade and investment policies in the implementation of the Monterrey Consensus : regional perspectives (United Nations, 2005)
"Papers and comments presented at the Expert Group Meeting on the Role of Trade and Investment Policies in the Implementation of the Monterrey Consensus : Bangkok, 26-27 October 2004."
"Sales No. E.05. II. F.15"--Title page verso
"ST/ESCAP/2363"--Title page verso
At foot of title: Economic and Social Commission for Asia and the Pacific
Keywords: International trade; Investments, Foreign -- Asia; Investments, Foreign -- Pacific Area; International trade.; Investments, Foreign.; Asia.; Pacific Area.